2014
DOI: 10.1080/00380768.2014.897924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil microorganisms on arsenite oxidation in paddy soils under oxic conditions

Abstract: The contribution of abiotic and biotic processes to the oxidation of arsenite [As(III)] when anaerobic paddy soils were shifted to oxic conditions was investigated. Soil slurries were first incubated under reducing conditions to allow indigenous arsenic (As) to be dissolved into the liquid phase as As(III), and were then switched to oxic incubation conditions with shaking. One day after switching to oxic incubation, As(III) almost disappeared from the liquid phase without any increase of arsenate [As(V)], sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…In their experiment, O 2 was supplied to a soil slurry via bubbling air. The oxidation speed of As-3 in our pot experiment was much slower than the speed estimated by Dong et al [33]. This difference was attributed to the slow and heterogeneous O 2 diffusion in the soil and Fe plaque of the rhizosphere in the rice-cultivated pot.…”
Section: Oxidation Of As After Drainagecontrasting
confidence: 51%
See 1 more Smart Citation
“…In their experiment, O 2 was supplied to a soil slurry via bubbling air. The oxidation speed of As-3 in our pot experiment was much slower than the speed estimated by Dong et al [33]. This difference was attributed to the slow and heterogeneous O 2 diffusion in the soil and Fe plaque of the rhizosphere in the rice-cultivated pot.…”
Section: Oxidation Of As After Drainagecontrasting
confidence: 51%
“…After drainage at harvest, part of the As-3 was oxidized over time, the proportion of As-S was decreased and the proportion of As-5 was increased. Dong et al [33] showed that the rate of oxidation of As-3 was 28-38% per day based on a microcosm experiment. In their experiment, O 2 was supplied to a soil slurry via bubbling air.…”
Section: Oxidation Of As After Drainagementioning
confidence: 99%
“…At various time intervals, soil slurry was centrifuged, and arsenic speciation in the supernatant was determined using high performance liquid chromatography (HPLC) (L-7000, Hitachi, Tokyo, Japan) with an Aminex HPX-87H ion exclusion column (Bio-Rad Laboratories, Hercules, CA, USA) under UV detection at 212 nm. In soil slurry spiked with 50 and 500 μM As(III), arsenic speciation and the total concentration of arsenic in the supernatant were determined by HPLC connected with a quadrupole inductively coupled plasma mass spectrometer (ICPMS) as described previously ( 8 , 45 ) because arsenic concentrations less than 1,000 μM cannot be measured by HPLC. An Inertsil ODS-3 column (4.6 × 150 mm; GL Science, Tokyo, Japan) was used for the separation of As(III) and As(V).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR products were cloned into the pMD 20-T vector using the Mighty TA-Cloning Kit (Takara Bio, Otsu, Japan) and transformed into DH5α chemically competent Escherichia coli (Takara Bio), according to the manufacturer’s instructions. Thirty to forty clones were randomly chosen from each soil slurry and were sequenced as described previously ( 8 ). The gene sequences obtained were aligned using the Clustal W program in MEGA version 6.0 ( 44 ) and clustered into operational taxonomic units (OTU), followed by grouping at more than 97% similarity based on different distances using Mothur ( http://www.mothur.org/ ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation